The comfort of knitted fabrics: interaction of sportswear and athlete’s body - Ivana Salopek Cubric; Goran Cubric; Vesna Marija Potocic Matkovic; Alenka Pavko Cuden (Communications in Development and Assembling of Textile Products, 2021)
The properties of the material used for the production of sportswear, as well as the properties of the sportswear, directly affect the heat exchange and sweat transfer that occurs at the interface between the skin and the environment. Thermography is a valuable method that provides insight into the patterns of temperature distribution on the surface of human skin that change during sports training or intense exercise. Such patterns can be further used to improve the design of sportswear. The experiment presented in this paper focuses on studying the changes in body temperature of the participating subjects during two typical types of training in football (condition training and tactical training). The duration of each training session was 60 minutes and measurements were taken after each of the total 10 training sessions. The thermal camera was used to measure the upper body temperatures of the players and the professional software was used for further processing of the thermal images. In the analysis of the thermal data, the average temperatures for 9 anterior and 9 posterior zones of the upper body were obtained. The results related to the changes in average temperature for each observed anterior and posterior zone and two types of football training are presented and discussed.